Aerial dance : a guide to dance with rope and harness - Davies, Jenefer (Routledge, an imprint of the Taylor & Francis Group, 2018)
"Aerial Dance: A Guide to Dance with Rope and Harness provides an introduction for the beginning aerialist. It covers rigging, equipment, advice on optimal conditioning, and a step-by-step guide to technique, including anatomical references, space and time considerations, and elements of force when working with and against gravity. Specific movements and choreography are framed anatomically and together reflect the pattern and order of an aerial technique class. Challenges inherent to this type of dancing are discussed, as well as wellness instruction and methods of altering these techniques for intermediate and advanced dancing. A companion website hosts video that corresponds with the technique and phrasing in the book."--Provided by publisher